The classification and reutilisation of recycled asphalt pavement binder: Norwegian case study - Xuemei Zhang; Hao Chen; Diego Maria Barbieri; Baowen Lou; Inge Hoff (Case Studies in Construction Materials, 2022)
With increased demand of asphalt pavement and limited binder and aggregate supply, the reutilisation of Recycled Asphalt Pavement (RAP) has gained more attention in pavement engineering from the environmental, sustainable, and economic views. Given this background, this study aims to classify and reutilise the recycled asphalt binder collected from Norwegian fields used for new asphalt pavement. For this purpose, three RAP binders (namely RAP-1, RAP-2, and RAP-3) extracted from the recycled asphalt pavement were categorised into two types of asphalt binders by comparing them with fresh asphalt binder 70/100 and long-term aged asphalt binder in terms of the physical, chemical, rheological, and mechanical properties. The specific treatments for the two types of RAP binder were proposed: Direct application of RAP-1 and RAP-2 binders as a replacement for fresh asphalt binder; and restoring RAP-3 binder by 4% rejuvenator to the same level as a fresh asphalt binder. Finally, the feasibility of three treated RAP binders for asphalt pavement was evaluated by analysing asphalt mixture performance. The results suggested that the three RAP binders can be applied to new asphalt pavements after proper treatments.